2010
DOI: 10.1021/ef100978n
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation into Combustion Characteristics of Two Sub-bituminous Coals in O2/N2and O2/CO2Environments

Abstract: There are still arguments on the coal combustion reactivity under conventional and oxy-coal combustion atmospheres. The selection of the experimental device in such a study is crucial. A laminar entrained flow reactor system that is capable of producing a similar combustion environment of a utility furnace in terms of the high heating rate and temperature was adopted in this study. This study investigated the characteristics of sub-bituminous coal combustion in its processes of devolatilization and char oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 11 publications
(31 reference statements)
1
18
0
Order By: Relevance
“…The results confirmed the previous findings obtained by various kinds of experimental methods (Chen et al 1994;Ponzio et al 2008;Shaddix and Molina 2009;Kim et al 2010;Qiao et al 2010). With a higher O 2 concentration, the mass diffusion of oxygen is stronger and less volatile matter concentration is needed for a mixture to be the flammable.…”
Section: Effect Of Gravity and Oxygen Concentrationsupporting
confidence: 90%
“…The results confirmed the previous findings obtained by various kinds of experimental methods (Chen et al 1994;Ponzio et al 2008;Shaddix and Molina 2009;Kim et al 2010;Qiao et al 2010). With a higher O 2 concentration, the mass diffusion of oxygen is stronger and less volatile matter concentration is needed for a mixture to be the flammable.…”
Section: Effect Of Gravity and Oxygen Concentrationsupporting
confidence: 90%
“…Lau and Niksa [65,66] for a 100 µm bituminous coal particle (they predicted a flame duration of 6.5 ms at 21% O 2 , T furnace =1250 K), again upon extrapolation to the higher temperature conditions that were used at the authors' laboratory. In simulated oxy-fuel combustion conditions (O 2 /CO 2 mixtures), the volatile flame durations are drastically shortened as oxygen mole fraction increases beyond the air level (21%) to 100% [15], which is also true in O 2 /N 2 mixtures (see also Murphy and Shaddix [40]; Molina and Shaddix [41], Kim et al [45], Khatami et al [16]). The effect of the background gas on the volatile flame duration was not as significant and was not always discernible [67]; lengthier flame durations were observed in the case of bituminous coals burning in CO 2 than in N 2 [14,67], but this was not observed in the case of sub-bituminous coals burning in CO 2 .…”
Section: Combustion Parametersmentioning
confidence: 83%
“…In parallel investigations, Shaddix and co-workers used the Sandia laminar entrained flow reactor to conduct comprehensive studies on the combustion of coals and chars of various ranks at oxygen partial pressures spanning 12-36%, in nitrogen and carbon dioxide [40][41][42]. Concurrently, Zhang et al [43,44] studied the combustion behavior of streams of a Victorian brown coal in a DTF, whereas Kim and coworkers [45] examined the combustion characteristics of sub-bituminous coals. Recently, Lee and Choi [46] recorded the volatile phase combustion characteristics of bituminous particles as a function of their size.…”
Section: Introductionmentioning
confidence: 99%
“…Varhegyi et al [43] found that the reaction rate of char-CO 2 is slower than char-O 2 at temperatures up to 1223 K. Other researchers [37,44] have found that the reactivity of char in O 2 /CO 2 conditions may be increased due to the high CO 2 concentrations at high temperatures (up to 1600 K).…”
Section: Resultsmentioning
confidence: 98%